Production of Four 15N-Labelled Cobalamins via Biosynthesis Using Propionibacterium freudenreichii - Wang, Mengle; Asam, Stefan; Chen, Jianqi; Ehrmann, Matthias; Rychlik, Michael (Frontiers in Microbiology, 2021)
Cobalamins (vitamin B12) are required by humans for their essential roles as enzyme cofactors in diverse metabolic processes. The four most common cobalamin vitamers are hydroxocobalamin (OHCbl), adenosylcobalamin (AdoCbl), methylcobalamin (MeCbl), and cyanocobalamin (CNCbl). Humans are not able to synthesise cobalamins de novo and thus must acquire them from external sources. Therefore, a reliable and robust analytical method to determine the cobalamins in dietary sources is highly required. For such a purpose, stable isotope dilution assays (SIDAs) with LC-MS/MS are most suited due to their superior sensitivity, specificity, and ability to compensate for matrix effects and analyte loss during sample work-up. However, a critical bottleneck for developing a SIDA method for cobalamins is the availability of stable isotope-labelled internal standards. In the present study, we harnessed the potential of Propionibacterium (P.) freudenreichii for the biosynthesis of 15N-labelled cobalamins. First, we developed a chemically defined medium (CDM) containing ammonium sulphate as a single nitrogen source except three essential vitamins that supported long-term stable growth of P. freudenreichii throughout continuous transfers. The CDM was further optimised for cobalamin production under different incubation schemes. With the optimised CDM and incubation scheme, fully 15N-labelled cobalamins were obtained in P. freudenreichii with a final yield of 312 ± 29 μg/L and 635 ± 102 μg/L, respectively, for [15N]-OHCbl and [15N]-AdoCbl. Additionally, an optimised incubation process under anaerobic conditions was successfully employed to produce specifically labelled [15N, 14N2]-cobalamins, with a yield of 96 ± 18 μg/L and 990 ± 210 μg/L, respectively, for [15N, 14N2]-OHCbl and [15N, 14N2]-AdoCbl. The labelled substances were isolated and purified by solid phase extraction and semi-preparative HPLC. Chemical modifications were carried out to produce [15N]-CNCbl and [15N]-MeCbl. Eventually, 15N-labelled compounds were obtained for the four cobalamin vitamers in high chromatographic and isotopic purity with desired 15N-enrichment and labelling patterns, which are perfectly suited for future use in SIDAs or other applications that require isotopologues.